A Role for NADPH Oxidase in Antigen Presentation - Gardiner, Gail J.; Deffit, Sarah N.; McLetchie, Shawna; Pérez, Liliana; Walline, Crystal C.; Blum, Janice S. (Frontiers in Immunology, 2013)
The nicotinamide adenine dinucleotide phosphate (NADPH) oxidase expressed in phagocytes is a multi-subunit enzyme complex that generates superoxide (O2.-). This radical is an important precursor of hydrogen peroxide (H2O2) and other reactive oxygen species (ROS) needed for microbicidal activity during innate immune responses. Inherited defects in NADPH oxidase give rise to chronic granulomatous disease (CGD), a primary immunodeficiency characterized by recurrent infections and granulomatous inflammation. Interestingly, CGD, CGD carrier status, and oxidase gene polymorphisms have all been associated with autoinflammatory and autoimmune disorders, suggesting a potential role for NADPH oxidase in regulating adaptive immune responses. Here, NADPH oxidase function in antigen processing and presentation is reviewed. NADPH oxidase influences dendritic cell (DC) crosspresentation by major histocompatibility complex class I molecules (MHC-I) through regulation of the phagosomal microenvironment, while in B lymphocytes, NADPH oxidase alters epitope selection by major histocompatibility complex class II molecules (MHC-II).